Taxonomic corrections on Cronion (Hemiptera: Heteroptera: Plataspidae) - Rédei, Dávid (Zootaxa, 2017)
Vollenhoven (1864) presented a preliminary report and subsequently (Vollenhoven 1865) a detailed description of a new genus of pentatomoid true bugs (Hemiptera: Heteroptera), Poseidon Vollenhoven, 1864, with a single included species, P. malayanus Vollenhoven, 1864; the species is therefore the type species of the genus by monotypy. The genus was placed into Scutelleridae by Vollenhoven (1864, 1865), but the latter taxon was defined broadly, in a way much different from the current concept of this family (see e.g. Rider et al. 2017); Stål (1876) transferred it into Plataspidae defined in the present sense. Bergroth (1891) showed that Poseidon was preoccupied by Poseidon Girard, 1825, a valid genus of ribbon worms (Nemertea), and therefore he proposed a replacement name, Cronion Bergroth, 1891, for it. Miller (1955) described another new plataspid genus, Triodocoris Miller, 1955, and designated the newly described T. cinctus Miller, 1955, as its type species. Both of these genera have remained monotypic, and no author have presented new data on them since their original descriptions.